Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
previousshortDOI: 10/ghgk6v previousDOI: 10.5281/zenodo.3346903 EdTechHub.Source: 2405685:3BG5X7VG EdTechHub.Source: <this> shortDOI: 10/ghgk6v KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3346903 10.53832/edtechhub.0017 10/ghgk6v 2129771:FLGEYF22 2339240:SZ4GSDD6 2405685:3BG5X7VG
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
previousShortDOI: 10/ghgnfn previousShortDOI: 10/ghgnfn previousDOI: 10.5281/zenodo.4779020 previousDOI: 10.5281/zenodo.4768577 previousDOI: 10.5281/zenodo.3594489 previousShortDOI: 10/ghgnfn EdTechHub.Copy: 2129771:USWMWK73 previousShortDOI: 10/ghgnfn KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523943 10.5281/zenodo.3594489 10.5281/zenodo.4768577 10.5281/zenodo.4779020 10.53832/edtechhub.0015 10/ghgnfn 2129771:K852X3EV 2129771:T7BUZI5N 2129771:USWMWK73 2339240:5KS58AH6 2339240:NZDE37HY 2405685:NM6CPLE9 2405685:SSWKT2MV 2405685:TDVP3W34
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology; EdTech; low-income countries; literature review